Regulation of endothelial progenitor cell homing after arterial injury - Hristov, Mihail; Zernecke, Alma; Liehn, Elisa A.; Weber, Christian (Thrombosis and Haemostasis, 2007)
Adult bone marrow and peripheral blood contain sub-populations of vascular precursor cells, which can differentiate into mature endothelial cells and have therefore been commonly termed endothelial progenitor cells (EPCs). Although EPCs encompass rather heterogeneous cell sub-populations of multiple origins and localization, these cells were basically characterized by expression of progenitor markers and by the development of colony-forming units and late endothelial outgrowth with terminal differentiation into mature endothelial cells. Notably, functional studies in vivo have implied the contribution of EPCs to therapeutic reendothelialization and inhibition of neointimal growth following endothelial injury. In the context of this regenerative arterial remodeling, an adequate homing of EPCs plays a central role. This multi-step process of EPC mobilization, recruitment and firm adhesion is regulated by key angiogenic chemokines (CCL2, CXCL1, CXCL7, CXCL12) and their respective receptors (CCR2, CXCR2, CXCR4). Furthermore, the recruitment of circulating EPCs to sites of arterial injury is synchronized by activated platelets and adhesion molecules of the selectin and integrin family. Thus, translating this molecular knowledge to interventional cardiovascular medicine,such a detailed understanding in the complex regulation of EPC homing may be helpful for more effectively preventing “in-stent” stenosis by facilitating stent endothelialization.
Keywords: Adhesion molecules; atherosclerosis; endothelial cells